2013
DOI: 10.1111/imb.12060
|View full text |Cite
|
Sign up to set email alerts
|

De novo characterization of the Dialeurodes citri transcriptome: mining genes involved in stress resistance and simple sequence repeats (SSRs) discovery

Abstract: The citrus whitefly, Dialeurodes citri (Ashmead), is one of the three economically important whitefly species that infest citrus plants around the world; however, limited genetic research has been focused on D. citri, partly because of lack of genomic resources. In this study, we performed de novo assembly of a transcriptome using Illumina paired-end sequencing technology (Illumina Inc., San Diego, CA, USA). In total, 36,766 unigenes with a mean length of 497 bp were identified. Of these unigenes, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 61 publications
1
34
1
Order By: Relevance
“…The inferred functions of 28.5% of the unigenes were not resolved. There were differences compared with the transcriptomes of B. dorsalis (Shen et al ., ; Zheng et al ., ), and other insects (Dou et al ., ; Wei et al ., ; Chen et al ., ); however, the results were similar to those of the transcriptome of the midgut of B. dorsalis (Shen et al ., ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The inferred functions of 28.5% of the unigenes were not resolved. There were differences compared with the transcriptomes of B. dorsalis (Shen et al ., ; Zheng et al ., ), and other insects (Dou et al ., ; Wei et al ., ; Chen et al ., ); however, the results were similar to those of the transcriptome of the midgut of B. dorsalis (Shen et al ., ).…”
Section: Resultssupporting
confidence: 83%
“…A total of 20 107 distinct sequences (65.89% of all the unigenes) matched known genes that encoded functional proteins, suggesting that the assembly quality was high. The percentage of unigenes matching known proteins was much higher than those reported in the whole body transcriptome of B. dorsalis (55.1%; Shen et al ., ), Bemisia tabaci (16.2%; Wang et al ., ), Nilaparvata lugens (40.0%; Bao et al ., ), Plutella xylostella (22.3%; He et al ., ), L. entomophila (61.6%; Wei et al ., ) and D. citri (44.8%; Chen et al ., ), as well as for the tissue transcriptome of testis and male accessory glands in D. variabilis (30.9%; Sonenshine et al ., ). Amongst the 30 516 unigenes, almost a third shared no significant similarities to known genes and may be novel/or fast‐evolving sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 41,716 (68.96%) were not annotated and may represent genes without detectable homologies. The number of annotated unigenes is lower than the results reported by other research groups for other invertebrate species [23,24], indicating that our knowledge of P. pseudoannulata genes is limited. Further research is needed to characterize these genes and explore their functions.…”
Section: Resultscontrasting
confidence: 66%
“…Of these, the CYP4, CYP6 and CYP9 families have the largest number of genes. In a study of citrus whitefly, 17 P450s were found to belong to the CYP2, CYP3 and CYP4 families . Of 37 P450 transcripts from a B. tabaci population, most belonged to the CYP6 and CYP4 families .…”
Section: Discussionmentioning
confidence: 98%
“…The Delta family has the largest number of members, followed by the Sigma family. The largest family in the Trialeurodes vaporariorum transcriptome is Delta, but there are only three genes in the Delta family in the citrus whitefly . No Zeta and Epsilon family GSTs were found in Acyrthosiphon pisum and Myzus persicae transcriptomes .…”
Section: Discussionmentioning
confidence: 99%